Impact of etiology of chronic renal failure on growth in children - Sultana, S; Rahman, MH; Paul, SK; Hossain, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S34-39The abstract of this article is available on the PubMed website